Agriculture and adaptation in Bangladesh: Current and projected impacts of climate change - Thomas, Timothy S.; Mainuddin, Khandaker; Chiang, Catherine; Rahman, Aminur; Haque, Anwarul; Islam, Nazria; Quasem, Saad; Sun, Yun (International Food Policy Research Institute, 2013)
The goal of this research was to examine the likely impacts of climate change on agriculture in Bangladesh, and develop recommendations to policymakers to help farmers adapt to the changes. In this study, we use climate data from four general circulation models (GCMs) to evaluate the impact of climate change on agriculture in Bangladesh by 2050. We use the DSSAT (Decision Support System for Agrotechnology Transfer) crop modeling software to evaluate crop yields, first for the 1950 to 2000 period (actual climate) and then for the climates given by the four GCMs for 2050. We evaluate crop yields at 1,789 different points in Bangladesh, using a grid composed of roughly 10 kilometer (km) squares, for 8 different crops in 2000 and 2050. For each crop, we search for the best cultivar (variety) at each square, rather than limiting our analysis to a single variety for all locations. We also search for the best planting month in each square. In addition, we explore potential gains in changing fertilizer levels and in using irrigation to compensate for rainfall changes. This analysis indicates that when practiced together, using cultivars better suited for climate change and adjusting planting dates can lessen the impacts of climate change on yields, especially for rice, and in some cases actually result in higher yields. In addition, the analysis shows that losses in yield due to climate change can be compensated for, for many crops, by increasing the availability of nitrogen in the soil.